2013
DOI: 10.1541/jae.33.21
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric perturbations observed by the low altitude satellite DEMETER and possible relation with seismicity

Abstract: Abstract. The high-altitude ionospheric perturbations around the equatorial anomalies (EA) are often observed by DEMETER spacecraft on the nighttime orbits. The ionospheric perturbations are recognized as an enhancement of the electric field in the ELF frequency range in the satellite coordinate. Clear perturbations are mostly recognized on the dayside of the satellite orbit and the peak perturbation intensity tends to increase with increasing magnetic latitude based on around 1000 perturbation events observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This satellite result is likely to be consistent with the VLF finding by Hayakawa et al (). Another statistical study of ionospheric perturbations in relation with equatorial anomalies observed by DEMETER has been done by Hobara et al () using the electric field measurement, who have shown a weak correlation between nighttime ionospheric perturbations and land earthquakes. A similar work by Ryu et al () investigated the correlation between seismic activity and equatorial plasma density variations.…”
Section: Introductionmentioning
confidence: 99%
“…This satellite result is likely to be consistent with the VLF finding by Hayakawa et al (). Another statistical study of ionospheric perturbations in relation with equatorial anomalies observed by DEMETER has been done by Hobara et al () using the electric field measurement, who have shown a weak correlation between nighttime ionospheric perturbations and land earthquakes. A similar work by Ryu et al () investigated the correlation between seismic activity and equatorial plasma density variations.…”
Section: Introductionmentioning
confidence: 99%
“…Němec et al [21,22] carried out a statistical study using the data of the electric field up to 10 kHz, and the results show a clear decline (several sigma) of the wave intensity in a few hours preceding earthquakes, which was repeated with similar but less obvious (only two sigma) fall results by Píša et al [23,24]. Statistical study to investigate the relationship between seismicity and equatorial anomalies observed by DEMETER has been performed using electric field measurement [25] and equatorial plasma density [26]. He et al [27,28] statistically indicated that the electron density near the epicenter increased in the nighttime, and the intensity of anomalies enhancement was found when the magnitude increased.…”
Section: Introductionmentioning
confidence: 90%
“…Similar but less prominent (only two sigmas) results were also found by Píša et al (2012Píša et al ( ,2013. The correlation between the equatorial anomalies observed by DEMETER and seismic activities have been analyzed based on electric-field measurements (Hobara et al, 2013) and equatorial plasma density (Ryu et al, 2014a). Further, other statistical analyses using the complete DEMETER dataset have shown that the number of disturbances first increases and then gradually decreases during earthquakes (Li and Parrot, 2013;Yan et al, 2017;Parrot and Li, 2018;Xiong et al, 2020).…”
Section: Introductionmentioning
confidence: 54%